2015
DOI: 10.1016/j.cegh.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

How happy are pregnant women?: A socio-demographic analysis

Abstract: Introduction''To be pregnant is to be vitally alive, thoroughly woman, and undoubtedly inhabited''. 1 Greek philosopher Aristotle 2 believed that, happiness is the central purpose of human life and existence, and that one's virtues lead to happiness. He, thus, defines happiness as ''. . .the function of man is to live a certain kind of life, and this activity implies a rational principle, and the function of a c l i n i c a l e p i d e m i o l o g y a n d g l o b a l h e a l t h 3 ( 2 0 1 5 ) 1 1 7 -1 2 4 a r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Neshat-Doost et al also showed that marital satisfaction is associated with happiness during pregnancy (14). Also, Malhotra et al reported that pregnant women living in extended families and were supported by them had higher levels of happiness (9). Relationship between couples intimacy seems to get increasing marital satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Neshat-Doost et al also showed that marital satisfaction is associated with happiness during pregnancy (14). Also, Malhotra et al reported that pregnant women living in extended families and were supported by them had higher levels of happiness (9). Relationship between couples intimacy seems to get increasing marital satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, women with first-time pregnancy were found to be happiest 90.1 %. Also, the study of Malhotra et al showed that the happiness level reduced from 76.4% in women with first time pregnancy to 70.1% in the third time (9). Perhaps the drop in the level of happiness relates to concerns about childcare, feelings of anxiety, distress, and commitment to the other children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations